Banded dye murex, Hexaplex trunculus measurements of total weight, soft tissue weight and net calcification rate in males and females over the 310 day ocean acidification experiment - Sanja Gran; Sam Dupont; Luka Glamuzina; Ana Bratoš Cetinić (PANGAEA, 2025)
Physiological traits of banded dye murex were measured during the exposure to a range of pH over the course of 310 days. Gastropods were collected in Bistrina Bay, part of the Mali Ston Bay in the Southeastern Adriatic Sea (42°52 extquotesingle19.1 N 17°42 extquotesingle02.3 E). Experiment was performed in Laboratory for Mariculture, University of Dubrovnik. Banded dye murexes were maintained in nine treatment tanks (volume 130L) with a flow-through water system with filtered, UV-sterilized, and aerated ambient seawater pumped directly from the Bistrina Bay adjacent to the laboratory facilities. Nine pH treatments were assigned to tanks, ranging from pHT 7.95 to 7.22. pH was manipulated by bubling pure CO2 gas, controlled with pH computers (Milwaukee MC122).Temperature, salinity, dissolved oxygen concentration were measured using multiparametric probes (YSI Pro 30 & Oxygen Handy Polaris, respectively). pH was measured on a total scale (pHT) by the potentiometric method with TRIS (2-amino-2-hydroxy-1,3-propanediol) buffer. Total alkalinity (TA, μmol kg-1) was determined with the potentiometric two-point open-cell 0.1 M HCl titration. Other seawater carbonate chemistry parameters (pCO2, ΩCa, ΩAr) were calculated based on known TA and pHT for a given salinity using CO2SYS software. Measurments of total weight were performed eight times during the experiment: day 28, 59, 91, 133, 172, 196, 236 & 310. Total wet weight was measured to the nearest 0.01 g on the top-load scale (Mettler toledo JL602-G/L) for the same individuals nine times over the course of experiment. Prior to weighing, snails were placed on absorbent blotting paper for approximately 20 minutes to remove excess water. The procedure was repeated eight times during the experiment (day 28, 59, 91, 133, 172, 196, 236, 310). Total weight growth rate (TWGR in g day-1) was calculated for each individual as the change in the shell weight between successive observation points divided by time. Net calcification rate was measured with a buoyant weight technique where the weight of the whole snails in seawater (buoyant weight) was determined by placing them on an improvised holder made of copper wire attached directly to the hook at the bottom of scale (Mettler toledo JL602-G/L). The scale was placed on a stand with a hole in the centre, under which was the container of seawater. Immediately before weighing, the snails were carefully forced to close the operculum to clear their mantle cavities of possible air. The balance was tared to compensate for the weight of the improvised holder, and the weight of the submerged snails was recorded to the nearest 0.01 g. The procedure was repeated seven times during the experiment (day 59, 91, 133, 172, 196, 236, 310). To obtain estimates of shell weight from immersed weight, a regression between shell weight and buoyant weight was performed. Net calcification rate (NCR in g day-1) was calculated for each individual as the change in shell weight between successive observation points divided by time. The soft body weight was calculated for each gastropod as the difference between the total weight and the shell weight. Soft body growth rate (STWGR in g day-1) was calculated for each individual as the difference in soft body weight between successive observation points divided by time. At the end of the experiment, specimens from all treatments were sampled and frozen until further analysis. For the sex determination, shells were cracked with a vice to expose the soft tissue. Males were identified by the presence of a penis behind the right tentacle, females by the vaginal opening. As temperature was varying naturally over the course of the experiment, statistical analysis was divided into periods to account for the modulating effect of the temperature. Carbonate Chemistry data were downloaded from the PANGAEA dataset (see Source). In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2024-02-26.